Cytokine Profiles of Chronic Urticaria Patients and the Effects of Omalizumab Treatment - Ozge Can Bostan; Ebru Damadoglu; Basak Ezgi Sarac; Busra Kilic; Ümit Murat Sahiner; Cagatay Karaaslan; Gul Karakaya; Ali Fuat Kalyoncu (Mattioli1885, 2023)
Introduction: Cytokines are key mediators in immunological and inflammatory conditions, including chronic spontaneous urticaria (CSU). Objectives: To investigate Th1, Th2, and Th17 cytokine profiles in CSU and to evaluate the possible effect of omalizumab treatment. Methods: Patients who were followed up for CSU, as well as healthy volunteers, were included in the study. To assess urticaria activity, the 7-day-Urticaria Activity Score (UAS-7), the Urticaria Control Test (UCT), and the Chronic Urticaria Quality of Life Questionnaire (CU-QoL) were filled. Serum levels of IL-6, IL-17, IL-31, eotaxin, RANTES, TNF-α, and TSLP were analyzed by ELISA and compared in CSU and control groups. The patients were analyzed in two groups as the omalizumab group and the non-omalizumab group based on their treatment status.   Results: Total IgE, ESR, CRP, RANTES, and TNF-a were significantly different in the overall comparison of the three groups: CSU-receiving omalizumab, CSU-not receiving omalizumab, and control groups (P <0.01, 0.015, <0.01, <0.01 and <0.01 respectively). Total IgE, CRP, RANTES, and TNF-α values were similar in those who received and did not receive omalizumab, yet these biomarkers were significantly higher in both groups than in the control group (P < 0.05). Statistical significance in ESR was observed only between the CSU-receiving omalizumab group and the control group (P = 0.01). Within the CSU patients, there was a slight but significant correlation between UCT and TNF-α (P = 0.008, r = 0.32) and IL-17 (P = 0.06, r = 0.33) levels. Conclusions: The investigated cytokine profile in CSU patients may differ from healthy controls, particularly with the higher levels of RANTES and TNF-α, and omalizumab treatment does not seem to affect that profile in CSU patients.